Cyclometalated Complexes of Platinum(II) with 2‐Vinylpyridine. Issue 13 (20th March 2014) - Zucca, Antonio; Maidich, Luca; Carta, Veronica; Petretto, Giacomo L.; Stoccoro, Sergio; Agostina Cinellu, Maria; Pilo, Maria I.; Clarkson, Guy J.
Abstract: The electron‐rich platinum(II) derivatives [Pt(R)2 (DMSO)2 ] (R = Me, Ph) react with 2‐vinylpyridine (L) to give the cyclometalated complexes [Pt(L–H)(R)(DMSO)] through C–H bond activation. Cyclometalation also occurs with [Pt(Me)(Cl)(DMSO)2 ]. From the starting compounds, a series of cyclometalated complexes was obtained and characterised by analytical and spectroscopic methods. The molecular structures of [Pt(L–H)(Me)(PPh3 )] and [Pt(L–H)(Ph)(PCy3 )] were solved by X‐ray diffraction analysis, and the results unambiguously demonstrate cyclometalation of 2‐vinylpyridine. The five‐membered cyclometalated ring is particularly stable, likely due to partial electronic delocalisation. Abstract : The synthesis, and analytical and spectroscopic characterization of a series of cyclometalated complexes of platinum(II) with 2‐vinylpyridine (L) is reported in detail. The five‐membered cyclometalated ring is particularly stable, likely due to partial electronic delocalisation.